Goat intake, diet selection and milk quality as affected by grazing time of day - Avondo M.; Bonanno A.; Pagano R.; Di Grigoli A.; Giambalvo D.; Alicata M.L. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Sixteen Girgentana lactating goats were divided in two experimental groups and housed in individual pens where they received 500 g/d of barley grain. The goats were left to graze on a Lolium sward, as follows: group 1, from 9:00 to 13:00; group 2, from 12:00 to 16:00. Herbage water-soluble carbohydrates (WSC) increased in the afternoon, whereas herbage crude protein (CP) content slowly decreased. However, selective behaviour allowed the morning group to assume a diet much higher in CP than the afternoon group (19.8 vs 16.7% DM). Pasture DM intake resulted significantly higher in the afternoon (825.4 vs 748.8 g/day; P
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)